(untitled) (Itinera, 2025)
This article explores the pivotal role of aesthetic experience, emotions, and relationality in Arne Næss’s philosophy of Deep Ecology. Challenging the traditional dualism between reason and emotion, the paper argues that ecological awareness and ethical commitment emerge from an embodied, aesthetic mode of engagement with the world. Drawing on phenomenological insights and Gestalt theory, it highlights how perceiving the environment as an interconnected whole transforms the subject’s sense of self and fosters a joyful, affective connection with nature. For Næss, reconnecting with these essential relationships involves a deep understanding that our very identities are intricately shaped by the ecological contexts in which we dwell. The fresh air we breathe, the nourishing food we consume, and the diverse environments we inhabit each contribute to the essence of who we are as individuals. This vision resonates powerfully with the Stoic concept of oikeiosis, which emphasises the importance of growing familiar with and emotionally attuned to the world around us, fostering a sense of belonging within it. Within this rich framework, emotions play a crucial role. Central to this argument is the concept of hilaritas – the joyous recognition of belonging to the broader ecological community, which grounds ecological responsibility and sustained environmental action. By situating Næss’s ecosophy within a wider philosophical lineage that includes Spinoza and contemporary theories of atmosphere and affect, the article proposes an ecological aesthetics that is simultaneously a practice of ethical relationality and embodied joy. This approach offers new perspectives on how aesthetic sensibility can catalyse deeper environmental engagement in the Anthropocene.